GEOTHERMAL ENERGY: A CLEAN, RELIABLE AND EFFICIENT SOURCE OF ENERGY - Siddikov Rasuljon Uktamovich; Baxriddinova Dilnora Sharifjon kizi; Xusanova Sarvinoz Alisher kizi (American Journals, 2023)
In this article, we will take a closer look at the advantages of geothermal energy as a cleaner, more reliable and efficient source of energy.
Keywords: geothermal energy, clean energy, renewable energy, geothermal power plants, heat pumps, sustainable energy, geothermal resources